Far from the madding civilization: Anarcho-primitivism and revolt against disintegration in Eugene O’Neill’s The Hairy Ape - Jeihouni, Mojtaba; Maleki, Nasser (International Journal of English Studies, 2016)
Anarcho-primitivism contends that modern civilization deprives people of their happiness, which is why it seeks to reconstruct civilization on a primitive basis, one that holds concrete promises of happiness. It argues that a harmonious relation with human nature and external nature needs to be established by translating technological societies into societies that are free of hierarchy, domination, class relationships, and, simply put, of modern structures. Anarcho-primitivists intend to reinstate a primitive outlook in the modern era and recover the authenticity and wholeness lost to the tyranny of civilization. The radical nature of Yank’s anti authoritarianism in Eugene O’Neill’s The Hairy Ape (1921) demonstrates that he is totally at a loss about the positive functions of industrialism. We argue that Yank expresses a deep resentment toward civilization that is barely hidden in the play. This leads us to suggest that Yank’s objective is not dissimilar from that of anarcho primitivists: he values his individuality and tries to subvert the social forces that are arrayed against it. Like anarcho-primitivists, he is determined to bring down the pillars of the material culture in favor of a primitive life, where free subjectivity or individuation becomes the integral gift of society.